Concepts and relevance of genome-wide association studies. (1st March 2016) - Scherer, Andreas; Christensen, G. Bryce
Genome-wide association study (GWAS) technology has been a primary method for identifying the genes responsible for diseases and other traits for the past 10 years. Over 2, 000 human GWAS reports now appear in the scientific journals. The technology is continuing to improve, and has recently become accessible to researchers studying a wide variety of animals, plants and model organisms. Here, we present an overview of GWAS concepts: the underlying biology, the origins of the method, and the primary components of a GWAS experiment.